Bacille Calmette–Guerin Complications in Newly Described Primary Immunodeficiency Diseases: 2010–2017 - Nunes-Santos, Cristiane de Jesus; Rosenzweig, Sergio D. (Frontiers in Immunology, 2018)
Bacille Calmette-Guerin (BCG) vaccine is widely used as a prevention strategy against tuberculosis. BCG is a live vaccine, usually given early in life in most countries. While safe to most recipients, it poses a risk to immunocompromised patients. Several primary immunodeficiency diseases (PIDD) have been classically associated to complications related to BCG vaccine. However, a number of new inborn errors of immunity have been described lately in which little is known about adverse reactions following BCG vaccination. The aim of this review is to summarize the existing data on BCG-related complications in patients diagnosed with PIDD described since 2010. When BCG vaccination status or complications were not specifically addressed in those manuscripts, we directly contacted the corresponding authors for further clarification. We also analyzed data on other mycobacterial infections in these patients. Based on our analysis, around 8% of patients with gain-of-function mutations in STAT1 had mycobacterial infections, including localized complications in 3 and disseminated disease in 4 out of 19 BCG vaccinated patients. Localized BCG reactions were also frequent in activated PI3K! syndrome type 1 (3/10) and type 2 (2/18) vaccinated children. Also, of note, no BCG related complications have been described in either CTLA4 or LRBA deficient patients; and not enough information on BCG vaccinated NFKB1 or NFKB2 deficient patients was available to drive any conclusions about these diseases. Despite the high prevalence of environmental mycobacterial infections in GATA2 deficient patients, only one case of BCG reaction has been reported in a patient who developed disseminated disease. In conclusion, BCG complications could be expected in some particular, recently described PIDD and it remains a preventable risk factor for pediatric PIDD patients.